DVD Reviews - Wagner, Kristen Anderson and Sterritt, David and Dillon, Steven and Porton, Richard and Andersson, Lars Gustaf and McSweeney, Terence (Film International, 2008)
Treasures III: Social Issues in American Film (19001934) Various directors Curated by Scott Simmon Music curated by Martin Marks Runtime 738 minutes (4 discs) DVD USA, 2007 Produced by the National Film Preservation Foundation Released by Image Entertainment (Region 0) Aspect Ratio 1.33:1 Sound Mix Two-track stereo Extras Audio commentary on most films. 173-page book of programme notes by Simmon and music notes by Marks, as well as photos, preservation information, and suggestions for further reading and viewing. Regular Lovers (Les Amants rguliers) (2005) France Director Philippe Garrel Screenplay Philippe Garrel, Arlette Langmann, Marc Cholodenko Producer Gilles Sandoz Cinematography William Lubtchansky Film Editing Franoise Collin, Philippe Garrel with Alexandra Strauss Sets Nikos Meletopoulos, Mathieu Menut Costumes Justine Pearce with Ccile Bergs Music Jean-Claude Vannier Choreography Caroline Marcad Sculptures Apel-les Fenosa Paintings Grard Garouste (reproduced by Gino Diomaiuto) With Louis Garrel (Franois), Clotilde Hesme (Lilie), Julien Lucas (Antoine), Mathieu Genet (Nicolas), ric Rulliat, Nicolas Bridet, Rassa Mariotti, Caroline Deruas-Garrel, Rebecca Convenant, Marie Girardin, Maurice Garrel, Ccile Garcia Fogel, Marc Barb, Nicolas Maury, Brigitte Sy, Nicolas Chupin, Martine Schambacher Runtime 175 minutes DVD USA, 2007 Produced and Distributed by Zeitgeist Films (Region 1) Aspect Ratio 1.33:1 Sound Mix Dolby SR Extras New transfer in original full-screen theatrical aspect ratio. Venice Film Festival press conference with Philippe Garrel, Louis Garrel, Clotilde Hesme and Gilles Sandoz, with English voice-over. Philippe Garrel filmography. French theatrical trailer. Optional English subtitles. Essay booklet by Kent Jones. The Angelic Conversation (1985) UK Director Derek Jarman Screenplay Selected sonnets by William Shakespeare read by Judi Dench Producer James Mackay Cameras Derek Jarman and James Mackay Production Design Christopher Hobbs With Paul Reynolds, Philip Williamson, Dave Baby, Timothy Burke, Simon Costin, Christopher Hobbs, Philip Macdonald, Toby Mott, Steve Randall, Robert Sharp, Tony Wood Runtime 78 minutes DVD UK, 2007 Produced and Distributed by The British Film Institute (Region 2) Aspect Ratio 1.33:1 Extras Interviews with James Mackay and Christopher Hobbs. Derek Jarman in Conversation with Simon Field (1989, 32 minutes). Stills gallery. Booklet includes introductory essay by Colin MacCabe. Caravaggio (1986) UK Director Derek Jarman Screenplay Derek Jarman Producer Sarah Radclyffe Director of Photography Gabriel Beristain Production Design Christopher Hobbs Costume Designer Sandy Powell With Nigel Terry (Caravaggio), Sean Bean (Ranuccio), Garry Cooper (Davide), Dexter Fletcher (Young Caravaggio), Spencer Leigh (Jerusaleme), Tilda Swinton (Lena), Nigel Davenport (Giustiniani), Robbie Coltrane (Scipione Borghese), Michael Gough (Cardinal del Monte) Runtime 93 minutes DVD UK, 2007 Produced and Distributed by The British Film Institute (Region 2) Aspect Ratio 1.85:1 Extras Interviews with Tilda Swinton, Nigel Terry and Christopher Hobbs. Commentary by Gabriel Beristain. Film and audio interviews with Derek Jarman. Gallery of storyboards, production sketches and Jarman's notebooks. Booklet includes introductory essay by Colin MacCabe. Wittgenstein (1993) UK Director Derek Jarman Screenplay Derek Jarman, Terry Eagleton and Ken Butler Producer Tariq Ali Director of Photography James Welland Costume Designer Sandy Powell With Karl Johnson (Wittgenstein), Michael Gough (Bertrand Russell), Tilda Swinton (Ottoline Morrell), John Quentin (John Maynard Keynes), Kevin Collins (Johnny), Clancy Chassay (Young Wittgenstein) DVD UK, 2007 Aspect Ratio 1.66:1 Extras Interviews with Tilda Swinton, Karl Johnson and Tariq Ali. Behind-the-scenes footage. Filmed introduction by Ian Christie. The Clearing (Alexis Bistikas, 1994, 7 minutes), a short film featuring Derek Jarman. Illustrated booklet includes introductory essay by Colin MacCabe. WR: Mysteries of the Organism (1971) Yugoslavia/Germany Director Dusan Makavejev Screenplay Dusan Makavejev Producer Dusan Makavejev Directors of Photography Pega Popovic (Yugoslavia), Aleksandar Petkovic (United States) With Milena Dravic (Milena), Ivica Vidovic (Vladimir Ilyich), Jagoda Kaloper (Jagoda), Tuli Kupferberg (Street Theatre Marine), Zoran Radmilovic (Radmilovic), Jackie Curtis (Himself/Herself). Runtime 85 Minutes DVD US, 2007 Produced and Distributed by The Criterion Collection (Region 1) Aspect Ratio 1.33:1 Extras Audio commentary assembled from Raymond Durgnat's 1999 book on the film Hole in the Soul , Makavejev's 1994 tragicomic autobiographical short film, originally made for the BBC. New and archival video interviews with Makavejev. Booklet includes an essay by critic Jonathan Rosenbaum. Sweet Movie (1974) Canada/France/West Germany Director Dusan Makavejev Screenplay Dusan Makavejev Producers Richard Hellman, Vincent Malle Director of Photography Pierre Lhomme With Carole Laure (Miss Monde 1984/Miss Canada), Pierre Clmenti (Potemkin Sailor), Anna Prucnal (Anna Planeta, Captain Ann), Sami Frey (El Macho), John Vernon (Mr Kapital) Runtime 98 Minutes DVD US, 2007 Produced and Distributed by The Criterion Collection Aspect Ratio 1.66:1 Extras New video interviews with Makavejev and Balkan film scholar Dina Iordanova. Actress Anna Prucnal sings a song from the film. A booklet featuring essays by critic David Sterritt and Harvard professor and philosopher Stanley Cavell. British Artists' Films: Ian Breakwell (19732007) UK Anthology includes Repertory , Excerpts from the Diary , The News , Growth , The Walking Man , Auditorium and Variety Director/Producer/Camera/Editor Ian Breakwell DVD UK, 2007 Distribution BFI (Region 2) Runtime 127 minutes Aspect Ratio 1.33:1 Extras theFrame: Ian Breakwell (2007, 32 mins), extensive illustrated interview recorded shortly before Breakwell's death. Illustrated 20-page booklet with a fully annotated filmography and a bibliography. Sleeve notes featuring a specially commissioned introductory essay by Will Self. Overlord (1975) UK Director Stuart Cooper Screenplay Christopher Hudson and Stuart Cooper Cinematography John Alcott Editor Jonathan Gili Music Paul Glass Producer James Quinn With Brian Stirner (Tom), Davyd Harries (Jack), Nicholas Ball (Arthur), Julie Neesam (The girl), Sam Sewell (The trained soldier), John Franklyn-Robbins (Dad), Stella Tanner (Mum) Runtime 84 minutes DVD USA, 2007 Distributed by The Criterion Collection (Region 1) Aspect Ratio 1.66:1 Audio English Dolby Digital 1.0 Monaural Extras New restored high-definition transfer. Audio commentary featuring Stuart Cooper and actor Brian Stirner . Mining the Archive , a new documentary featuring Imperial War Museum film archivists detailing the war footage used in the film. Capa Influences Cooper , a photo essay featuring Stuart Cooper on the photographer Robert Capa. A Test of Violence (1969), Cooper's short film about Spanish artist Juan Genovs. Cameramen at War (1943), the British Ministry of Information's tribute to newsreel and service unit cameramen. Germany Calling (1941), a British Ministry of Information propaganda film, clips of which appear in Overlord . Journals from two D-day soldiers, read by Brian Stirner. Theatrical trailer .
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjYuMy42MA